Three cases of neuromyelitis optica spectrum disorder - Matsusue, Eiji (Acta Radiol Open, 2016)
Neuromyelitis optica (NMO) is characterized by attacks of optic neuritis and longitudinally extensive transverse myelitis. Cases positive for aquaporin 4 antibodies are classified to NMO spectrum disorder (NMOSD) which includes cases with optic neuritis, transverse myelitis, or with brain lesions typical of NMO. Our three cases with NMO/NMOSD revealed five imaging features: (i) extensive transverse cord lesions, extending more than three vertebral segments, partially persisting as cavitation; (ii) periependymal lesions; (iii) lesions of the corticospinal tracts; (iv) extensive and confluent hemispheric white matter lesions reflecting vasogenic edema and partially involving the cerebral cortices and basal ganglia; and (v) two patterns of serial hemispheric white matter lesions: one is cavitation and another is partial regression or disappearance. Cavitations, in the upper spinal cord and hemispheric white matter, are considered to be caused by severe vasogenic edema and are likely to be one of the characteristic findings in NMOSD.